2020
DOI: 10.1002/1878-0261.12711
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA PGM5‐AS1 promotes epithelial‐mesenchymal transition, invasion and metastasis of osteosarcoma cells by impairing miR‐140‐5p‐mediated FBN1 inhibition

Abstract: Osteosarcoma is an uncommon tumor occurring in bone, accompanied by elevated incidence and reduced rate of healing. Epithelial-to-mesenchymal transition (EMT) serves as a conceptual paradigm to explain the invasion and metastasis of osteosarcoma and other cancers. Hence, developing effective therapeutic strategy to treat the EMT of osteosarcoma is essential. Here, we identified the molecular mechanism of long noncoding RNA (lncRNA) PGM5-AS1 in EMT and progression of osteosarcoma. Microarray-based analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are evolutionarily conserved RNA molecules longer than 200 bases that have no or limited protein-coding functions ( 6 , 7 ). Recent studies have shown that lncRNAs play an important role in the tumorigenesis and development of various cancers ( 8 , 9 ). LncRNAs are frequently dysregulated in EC tissues and participate in cancer progression ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are evolutionarily conserved RNA molecules longer than 200 bases that have no or limited protein-coding functions ( 6 , 7 ). Recent studies have shown that lncRNAs play an important role in the tumorigenesis and development of various cancers ( 8 , 9 ). LncRNAs are frequently dysregulated in EC tissues and participate in cancer progression ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs act as carcinogenic factors or tumor suppressor factors by regulating different mRNAs by sponging them ( 32 , 33 ). Several lncRNAs have been reported to be involved in OS progression ( 18 , 34 , 35 ). For example, as oncogenes, lncRNA PGM5-AS1 promotes epithelial-mesenchymal transition, invasion and metastasis of OS cells by impairing miR-140-5p-mediated fibrillin-1 inhibition ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lncRNAs have been reported to be involved in OS progression ( 18 , 34 , 35 ). For example, as oncogenes, lncRNA PGM5-AS1 promotes epithelial-mesenchymal transition, invasion and metastasis of OS cells by impairing miR-140-5p-mediated fibrillin-1 inhibition ( 34 ). On the other hand, lncRNAs can act as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNA PGM5‐AS1 is upregulated in osteosarcoma. It regulates the expression of miR‐140‐5p and FBN1 through sponge adsorption, thereby promoting tumor EMT, invasion, and metastasis 13 . LncRNA CCAT2, a marker of poor prognosis in patients with osteosarcoma, was found to promote EMT in osteosarcoma cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It regulates the expression of miR-140-5p and FBN1 through sponge adsorption, thereby promoting tumor EMT, invasion, and metastasis. 13 LncRNA CCAT2, a marker of poor prognosis in patients with osteosarcoma, was found to promote EMT in osteosarcoma cells. 14 Therefore, we also studied the relationship between lncRNA PVT1 and EMT in osteosarcoma cells.…”
mentioning
confidence: 99%